Effect of cable surface characteristics and flow turbulence on the aerodynamic behaviour of stay cables in dry conditions. Issue 207 (December 2020) - McTavish, Sean; D'Auteuil, Annick; Raeesi, Arash
Abstract: This article describes a wind-tunnel study to evaluate the aerodynamic behaviour of stay cables of a bridge with various surface geometries in dry conditions. Nine cable models were fabricated and tested. Aerodynamic forces acting on the static models were measured for different wind speeds, cable-wind angles and cable axial rotation angles, in smooth and turbulent flow. The aerodynamic forces of bare, round cable models with different roughness levels were used as a baseline to compare the aerodynamic loading of the cables with surface geometry features. A comprehensive database of existing and emerging cable geometries in a wide range of flow conditions and cable-wind angles was generated. The trends exhibited by models with geometric features are similar to results available in the open literature. The aerodynamic drag coefficient was largely affected by the presence of cable surface geometry. The model with helical strakes had the lowest drag coefficient throughout the range of Reynolds numbers that was evaluated. It was observed that turbulence had a similar effect on all models, resulting in a reduction of the drag coefficient at lower Reynolds numbers and an earlier increase in drag that is associated with the supercritical Reynolds number regime. The presence of turbulent flow resulted in higher drag coefficients at high Reynolds numbers. An important secondary finding was that models fabricated with the Selective Laser Sintering (SLS) technique have a higher surface roughness than high-density polyethylene (HDPE) stay cable sleeves but when printed, they have a similar surface roughness.